Development of Multicultural Islamic Religious Education Curriculum: A Literature Study on the Integration of Religious Moderation Values in Islamic Education - Kasmila Kasmila; Mirnawati Mirnawati; Muh. Sukirman; Nur Alifa Ranti; Nurindah Nurindah (Edusoshum : Journal of Islamic Education and Social Humanities, 2025)
Indonesia as a multicultural country faces serious challenges in managing diversity so that it does not develop into social conflicts and intolerant religious attitudes. In this context, Islamic Religious Education (PAI) has a strategic role in instilling the values of religious moderation through the development of an inclusive and contextual curriculum. This research aims to examine the concept of multicultural PAI curriculum development with an emphasis on the integration of religious moderation values in Islamic education. The research uses a qualitative approach with the type of library research. Data was obtained from primary sources in the form of the Qur'an, Hadith, as well as works by Islamic education scholars and thinkers, as well as secondary sources in the form of books, journal articles, and relevant education policy documents. Data analysis is carried out through content analysis and thematic analysis to formulate a conceptual framework for the development of a multicultural PAI curriculum. The results of the study show that the development of a multicultural PAI curriculum is a strategic need to systematically instill the values of tawassuth, tasamuh, i'tidal, and shura in the learning objectives, materials, and processes. This curriculum has positive implications for the formation of inclusive religious character, the prevention of religious extremism, and the strengthening of students' national commitments. This research confirms that the multicultural PAI curriculum based on religious moderation is an important foundation for the development of Islamic education that is relevant to the reality of a plural society and the challenges of the times.